2016
DOI: 10.1186/s12889-016-3650-4
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood environment correlates of physical activity and sedentary behavior among Latino adults in Massachusetts

Abstract: BackgroundU.S. Latinos experience high rates of cardio-metabolic diseases and have high rates of physical inactivity and sedentary behavior. Understanding the environmental factors associated with physical activity and sedentary behaviors among Latinos could inform future interventions. The purpose of this study is to explore the neighborhood environment correlates of physical activity and sedentary behavior in a sample of U.S. Latino adults.MethodsCross-sectional study of 602 Latino adults in Lawrence, MA. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 36 publications
4
17
0
Order By: Relevance
“…Results also confirm previous research showing that walking environment and safety are important neighborhood factors associated with PA engagement among adult populations (including Latinos) [11,12,[28][29][30][31]; nevertheless, not all studies have reported significant associations among these variables [32]. Lack of significant relationships among neighborhood factors of aesthetic quality, availability of healthy foods, violence, and activities with neighbors with PA were surprising given these factors intuitively appear to be related to PA and previous research suggest several of these factors as important determinants of PA [28,32,33]. Inconsistent findings across studies may be related to measurement, as previous research has used numerous methods to measure both neighborhood factors and PA [11].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Results also confirm previous research showing that walking environment and safety are important neighborhood factors associated with PA engagement among adult populations (including Latinos) [11,12,[28][29][30][31]; nevertheless, not all studies have reported significant associations among these variables [32]. Lack of significant relationships among neighborhood factors of aesthetic quality, availability of healthy foods, violence, and activities with neighbors with PA were surprising given these factors intuitively appear to be related to PA and previous research suggest several of these factors as important determinants of PA [28,32,33]. Inconsistent findings across studies may be related to measurement, as previous research has used numerous methods to measure both neighborhood factors and PA [11].…”
Section: Discussionsupporting
confidence: 89%
“…The finding that higher self-reported PA was associated with reduced risk for the presence of metabolic syndrome adds to the established body of research showing PA is an independent risk factor associated with development of cardiometabolic disease conditions (i.e., metabolic syndrome and cardiovascular disease) [2,5,6,27]. Results also confirm previous research showing that walking environment and safety are important neighborhood factors associated with PA engagement among adult populations (including Latinos) [11,12,[28][29][30][31]; nevertheless, not all studies have reported significant associations among these variables [32]. Lack of significant relationships among neighborhood factors of aesthetic quality, availability of healthy foods, violence, and activities with neighbors with PA were surprising given these factors intuitively appear to be related to PA and previous research suggest several of these factors as important determinants of PA [28,32,33].…”
Section: Discussionsupporting
confidence: 81%
“…To assess self-reported stress-related health problems, survey participants were presented with a list of stress-related health problems that are associated with chronic and neighborhood stress. 15 17 Survey participants were instructed to identify the stress-related health problems that they currently have and then rate how large of a problem it is to them (1= minimal problem, 2= moderate problem, 3= large problem). Lastly, to assess stress-related negative behaviors, survey participants were instructed to identify the stress-related negative behaviors that have the greatest impact on overall community health in their neighborhood.…”
Section: Methodsmentioning
confidence: 99%
“…Several reasons may account for this finding, such as the possibility that transport-or occupational-based physical activity is not being replaced by leisure walking in the neighborhood. Also, it is possible that streets in lower income neighborhoods have poorer sidewalk availability and quality, greater traffic volume, or higher crime, which can deter leisure walking [26]. Additional reasons for larger declines in step counts for individuals from lower income households may include being less likely to be able to afford home exercise equipment or access to online streaming exercises classes and being more negatively impacted by changes in employment or increased childcare requirements.…”
Section: Data Availability and Demographic Characteristicsmentioning
confidence: 99%